Pelestarian Permainan Tradisional Luko Gile (Bubu Gile) di Desa Dusun Baru 1 Kecamatan Pondok Kubang - Jevpri Yansa Putra; Rini Puspita Sari; Muhammad Arif Yusuf; Mallik Fadjar; Reni Wahyuni; Rahma Ardita; Vega Selviani; Indira Agleo Putri; Citra Widia Ningsih; Inna Rampasi (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to address the decline in interest and awareness among the younger generation in Desa Dusun Baru 1, Kecamatan Pondok Kubang, Kabupaten Bengkulu Tengah, regarding traditional cultural practices, particularly the Luko Gile (Bubu Gile) game. The purpose of this project is to preserve this traditional game and to reintroduce it to the community, especially to children and adolescents, as a means of fostering social interaction and cultural identity. The approach used includes community-based engagement centered around Masjid At-Taqwa, involving both local leaders and youth in training and activities designed to revitalize this cultural heritage. The method employed consists of direct observation, interviews with community leaders, and documentation of activities. The results demonstrate a significant increase in awareness and participation in the traditional game among the village youth, reflecting the effectiveness of the program in preserving local cultural heritage. The findings suggest the need for continuous and structured efforts to sustain this initiative.